CARCINOMA OF ORAL CAVITY AND OROPHARYNX IN SMOKELESS TOBACCO USERS OF ALL AGE GROUPS - Wahid, Abdul; Ahmad, Sajjad (Journal of Ayub Medical College Abbottabad, 1998)
Fifty cases clinically presenting with ulcerative lesions in oral cavity and oropharynx were biopsied. All cases histologically revealed carcinoma. The study included 25 males and 25 females. The age range was from below 20 years to above 50 years. There were 2 cases in age group up to 20 years, both were females. The maximum number of cases (28/50) was in age group 41-60 years. All cases had positive history of oral tobacco use in the form of naswar of variable duration and quantity. All the cases clinically presented with ulcerative lesions. The maximum number of cases was carcinoma gum (14/50). The next common site was tongue (10/50 cases). There were 7 cases of carcinoma of oropharynx. Histologically 48/50 cases were of squamous cell carcinomas of varying grades of differentiation. There was one malignant melanoma and one Adenocarcinoma.